The influence of Er:YAG laser irradiation on re-bonding shear bond strength of enamel. Issue 22 (17th November 2021) - Fang, Huimin; Teng, Caitian; Lu, Pengfei; Cao, Yang; Yu, Qing
Abstract: To investigate the effect of the erbium:yttrium:aluminum garnet (Er:YAG) laser on enamel re-bonding properties. 80 complete premolars and third molars were selected, after treatment, 120 failed enamel specimens were prepared and randomly divided into seven groups (16 samples for group A; 24 samples averaged to groups (B and C), the other 72 samples were divided into three groups (D) equally and the last four samples left for group (G). The groups (D) were divided into two parts (D121212) randomly and respectively. Two samples selected from each group were observed by Scanning Electron Microscope (SEM); Four samples (two of which were treated by acid-etching) selected from group (A) and two samples from the other each group were collected and compared with each other by Bioluminescence fluorescence imaging system (BFIS). The remaining 90 samples, the acid-etching treatment was carried out on groups (A111), while groups (D222) were not treated by acid-etching. Each group was subjected to re-bonding experiments, and the shear force was tested by a universal testing machine. The data of re-bonding strength of resin-enamel interfaces was calculated and recorded. The re-bonding strength of grinding group (B) and 5 Hz Er:YAG laser + etching group (D1) was the largest, followed by 5 Hz group, and that of the blank group (A) and sandblasting group (C) was the lowest. Compared with laser groups, the re-bonding strength of enamel after etching was higher than that without etching, and the strength became much stronger after 5 Hz Er:YAG laser irradiation. Er:YAG laser therapy might be considered as an alternative to conventional grinding in clinical enamel re-bonding therapy.